Pengaruh Footbath Therapy Terhadap Penurunan Skala Nyeri Pada Pasien Post Sectio Caesarea - Ana Karimatul Fikri; Yuni Astuti; Rusnaningsih Rusnaningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Childbirth through cesarean section can cause discomfort for the mother, one of which is pain arising from the abdominal incision wound. Footbath therapy is one of the methods that can be used to alleviate this pain. The purpose of this study is to evaluate the effectiveness of footbath therapy in reducing pain intensity in patients who have just undergone a cesarean section. This research uses a descriptive method with a case study design in the context of nursing care. The subjects of this study are two patients who have just undergone a cesarean section and are experiencing mild to moderate pain. The instruments used in this study are an observation sheet in the form of a PQRST pain assessment questionnaire, NRS (Numerical Rating Scale) pain scale measurement, and standard footbath therapy procedures. The research was carried out from 14 May 2024 to 15 May 2024 for the first respondent and for the second respondent it was carried out from 17 May to 18 May 2024 with implementation for 2 days and in 1 day it was carried out for 20 minutes. The results of this study showed that both respondents experienced a decrease in pain after giving footbath therapy. So this therapy has proven to be effective for post-cesarean section patients who experience pain.